Roles of HMGBs in Prognosis and Immunotherapy: A Pan-Cancer Analysis - Lin, Tong; Zhang, Yingzhao; Lin, Zhimei; Peng, Lisheng (Frontiers in Genetics, 2021)
Background: High mobility group box (HMGB) proteins are DNA chaperones involved in transcription, DNA repair, and genome stability. Extracellular HMGBs also act as cytokines to promote inflammatory and immune responses. Accumulating evidence has suggested HMGBs are implicated in cancer pathogenesis; however, their prognostic and immunological values in pan-cancer are not completely clear. Methods: Multiple tools were applied to analyze the expression, genetic alternations, the prognostic and clinicopathological relevance of HMGBs in pan-cancer. Correlations between HMGBs expression and tumor immune infiltrating cells (TIICs), immune checkpoints (ICPs) expression, microsatellite instability (MSI), and tumor mutational burden (TMB) in pan-cancer were investigated to uncover their interactions with the tumor immune microenvironment (TIME). Gene set enrichment analysis (GSEA) was conducted for correlated genes of HMGBs to expound potential mechanisms. Results: HMGBs expression was significantly elevated in various cancers. Both prognostic and clinicopathological significance was observed for: HMGB1 in ACC; HMGB2 in ACC, LGG, LIHC, and SKCM; HMGB3 in ESCA. Prognostic values were also found for: HMGB2 in KIRP and MESO; HMGB3 in BRCA, SARC, SKCM, OV, and LAML. The global alternation of HMGBs showed prognostic significance in ACC, KIRC, and UCEC. Furthermore, HMGBs were significantly correlated with TIICs infiltration, ICPs expression, MSI, and TMB in various cancers, indicating their regulations on the TIME. Last, results of GSEA illuminated genes positively correlated with HMGBs were similarly chromosome components participated in DNA activity-associated events. Conclusion: This study demonstrated HMGBs might be promising predictive biomarkers for the prognosis and immunotherapeutic response, also immunotherapy targets of multiple cancers.